Pembinaan Olimpiade Fisika untuk Meningkatkan Daya Saing Peserta Didik MAN 2 Tanah Datar - Handayani, Fitria; Putri, Yupita; Fitri, Dwi Rini Kurnia (TAFANI: Jurnal Pengabdian Masyarakat, 2025)
The Madrasah Science Competition and all other types of Olympic competitions are an important event to achieve achievements and a place for all students to show themselves. Debriefing before the competition is an important activity to carry out as a guide for students to take to the field. However, field facts state that in Man 2 Tanah Datar the coaching of Madrasah Science Competition physics experienced a few problems. Where there is a lack of interest and competitiveness of students at MAN 2 Tanah Datar in participating in Madrasah science competitions and National Student Olympiads in the field of physics at both district/city, provincial and national levels. If you stretch it backwards, this Madrasah Science Competition training is only carried out when it is approaching competition time. Therefore, this coaching can provide changes aimed at increasing students' self-confidence, by ensuring that anyone can take part in competitions, especially in the field of Physics Olympiads, as well as fostering students' interest in taking physics training long before taking part so that these students not only physically ready but also mentally ready. Apart from that, this coaching is carried out so that students are able to compete at any level without feeling burdened due to lack of preparation.